2023
DOI: 10.3390/ijms24055000
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of Homeodomain Leucine Zipper (HD-ZIP) Transcription Factor, Expression Analysis, and Protein Interaction of HD-ZIP IV in Oil Palm Somatic Embryogenesis

Abstract: Understanding the molecular mechanisms underlying somatic embryogenesis is essential for resolving the problems related to the long duration of the process and a low rate of somatic embryo induction in oil palm tissue culture. In this study, we conducted genome-wide identification of the oil palm homeodomain leucine zipper (EgHD-ZIP) family, which is one of the plant-specific transcription factors reported to be involved in embryogenesis. EgHD-ZIP proteins can be divided into four subfamilies, which have simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…HD-Zip TFs play a crucial role in affecting plant growth, development, and resilience to environmental stress [41]. To date, HD-Zip family genes have been systematically identified in several species, such as Chinese cabbage, chrysanthemum, oil palm, and watermelon [42][43][44][45]. Various studies have demonstrated that HD-Zip III and IV genes mainly contributed to shoot and root meristem development, as well as cell proliferation regulation.…”
Section: Discussionmentioning
confidence: 99%
“…HD-Zip TFs play a crucial role in affecting plant growth, development, and resilience to environmental stress [41]. To date, HD-Zip family genes have been systematically identified in several species, such as Chinese cabbage, chrysanthemum, oil palm, and watermelon [42][43][44][45]. Various studies have demonstrated that HD-Zip III and IV genes mainly contributed to shoot and root meristem development, as well as cell proliferation regulation.…”
Section: Discussionmentioning
confidence: 99%